2015
DOI: 10.4236/fns.2015.61014
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Marc of a Wild Tropical Plant <i>Tacca involucrata</i> (Schumach and Thonn, 1827)

Abstract: Tacca involucrata (Batflower or Polynesian arrowroot) tubers are a stable food in tropics where it occurs. In central Nigeria, it is processed locally after digging it from the ground by peeling with sharp sand, grating and soaking in fresh water after which it is filtered and the filtrate is dried and is cooked with other ingredients. The marc, said to be bitter, is usually discarded by deep burial as it is considered poisonous to livestock and humans. All parts of the plant are used in folk medicine to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It increases, as there are more carbon atoms and as chains get longer. The refractive index indicates that the sample may contain an unsaturated long carbon chain 44 . Measurements of the refractive index are particularly useful for determining the purity of volatile and fixed oils 45 .…”
Section: Discussionmentioning
confidence: 99%
“…It increases, as there are more carbon atoms and as chains get longer. The refractive index indicates that the sample may contain an unsaturated long carbon chain 44 . Measurements of the refractive index are particularly useful for determining the purity of volatile and fixed oils 45 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result tacca roots are found in local markets in many communities where they are traded and provide income for people harvesting, processing and trading in them. Bosha et al (2015) in a study carried out on the phytochemical analysis of tacca, reported the presence of reducing sugars, tannins, flavonoids, steroids, glycosides and hydrogen cyanide at 195.65 ± 0.5, 3.44 ± 0.2, 1.29 ± 0.5, 0.83 ± 0.4, 1.36 ± 1.0 and 0.00985 ± 0.3 (mg/100g), respectively. According to the authors, The elemental analysis of the root showed it to contain potassium, sodium, magnesium, selenium, manganese, vanadium and some heavy metals like lead, aluminium, arsenic and mercury at 36.45 ± 0.1, 44.04 ± 0.1, 1.52 ± 0.2, 0.80 ± 0.9, 0.52 ± 0.7, 0.27 ± 0.7, 0.07 ± 0.6, 0.008 ± 0.05, 0.085 ± 0.6 and 0.026 ± 0.6 (mg/100g), respectively.…”
Section: Conventional Uses Of T Inolucratamentioning
confidence: 98%
“…The flour from T. leontopetaloides of the present work was very rich in ash, compared with previous works by other authors (Tables 1 and 4), providing an indication of its richness in minerals. As macrominerals make up more than 0.005% of the human body and we require more than 100 mg of macrominerals per day , including calcium, magnesium, phosphorus, potassium, sodium and sulphur (Hark, 2005), the flour from T. leontopetaloides has potential to meet this dietary requirement, making it a good resource as food and feed (Bosha et al, 2015). Nevertheless, we observed that the method used to obtain the flour plays a major role not only in its ash content, but also in its mineral composition (Table 2).…”
Section: Inmentioning
confidence: 99%